APLIKASI METODE NEAREST NEIGHBOR PADA PENENTUAN JALUR EVAKUASI TERPENDEK UNTUK DAERAH RAWAN GEMPA DAN TSUNAMI - Era Madona; Muhammad Irmansyah (Elektron : Jurnal Ilmiah, 2013)
Indonesia located at a ring of fire was a country with the threat level earthquake and tsunami that is high. Various activities and socialization has done by government to prepare people to face all possibilities that happens during and after the earthquake and tsunami hit. Various facilities such as signs for evacuation instruction, simulation evacuation, and installation of alarm are prepared to assist in minimizing risk caused by tsunami and earthquake. This paper shows the system to determine shortest track in the tsunami evacuation routes in Padang West Sumatra. The selection of Padang is based on the earthquake disaster which tsunami potential ever happened in this town and claimed casualties quite a lot. In this paper, is selected the number of the track that can be follow when the citizens of the city of Padang would do the evacuation line of sector VI. Some of the selected path is shortest routes to secure areas in by pass road Padang. The shortest distance to the safe sector with the starter point Pasar Raya to road by pass is 9 km using the route - RS. Padang-Aisyiah Jl. Agus Salim-Jl. Sawahan GIS-Haru-Simpang Jl. Andalas-Jl. By pass